1997
DOI: 10.1074/jbc.272.41.25809
|View full text |Cite
|
Sign up to set email alerts
|

The Core Domain of HIV-1 Integrase Recognizes Key Features of Its DNA Substrates

Abstract: We investigated which features of the substrate specificity of human immunodeficiency virus type 1 (HIV-1) integrase could be assigned to the central domain of the 288-residue HIV-1 integrase protein, composed of amino acids 50 -212. This domain contains the active site and shares structural homology with a large family of polynucleotidyl transferases. Using model substrates with defined alterations in critical features we found that this domain alone is sufficient for recognition of: 1) the phylogenetically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
41
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 44 publications
6
41
0
Order By: Relevance
“…The reaction condition was identical to that described earlier in tion event (44,52). This DNA-binding region recognizes key features of viral DNA substrates and may be responsible for viral DNA specificity (19,41,52). In addition to viral DNA, UV cross-linking studies with HIV-1 integrase and a dumbbell disintegration substrate have identified residues 49 -69 and 139 -152 to be in close proximity to target DNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction condition was identical to that described earlier in tion event (44,52). This DNA-binding region recognizes key features of viral DNA substrates and may be responsible for viral DNA specificity (19,41,52). In addition to viral DNA, UV cross-linking studies with HIV-1 integrase and a dumbbell disintegration substrate have identified residues 49 -69 and 139 -152 to be in close proximity to target DNA.…”
Section: Discussionmentioning
confidence: 99%
“…C, PCR-based assay. The reaction condition was identical to that described earlier in tion event (44,52). This DNA-binding region recognizes key features of viral DNA substrates and may be responsible for viral DNA specificity (19,41,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disintegration substrates, such as the dumbbell used in Figs. 2 and 3, mimic integration intermediates and thus should occupy both the donor and target DNA binding sites in the active complex (27)(28)(29). L-731,988 was not bound in the presence of disintegration substrates, suggesting that the target DNA may occupy a site required for DKA binding.…”
Section: The Dka Binding Site Overlaps With the Target Dna Binding Simentioning
confidence: 99%
“…High-affinity binding (i) requires assembly on specific viral DNA donor substrates, with the U5 end preferred over U3, (ii) is competed with by DNAs that are competent to serve as target substrates for strand transfer or occupy the target site in the context of the disintegration reaction (7,(27)(28)(29), and (iii) requires an intact integrase catalytic center in the context of an active multimer. The ability to function as a donor substrate in strand transfer and 3Ј processing correlates with the ability to promote inhibitor binding because the U5 end is more efficient than U3 in both contexts (20).…”
Section: The Dka Binding Site Overlaps With the Target Dna Binding Simentioning
confidence: 99%